2016
DOI: 10.1515/mammalia-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability predicts frugivorous bat abundance in an urban environment

Abstract: We used a mathematical model based on nutrient availability to predict

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These results are similar to those reported by Flynn et al., (2009), who found in a global meta‐analysis that the FD of nectarivorous birds may be retained in human‐dominated landscapes because of potential surplus flower availability in those environments. Also, the prevalence of some functional groups of fruit‐eating bats in deforested landscapes has been explained as the result of high dispersal capability and an ability to exploit the food supply provided by fruit trees, such as Ficus spp., in urban contexts (Farneda et al., 2015; Gonçalves et al., 2017; Jara‐Servín, Saldaña‐Vázquez, & Schondube, 2016; Klingbeil & Willig, 2009). For instance, deforestation may generate a variety of patches with different successional stages, which might increase fruit availability for several functional groups of phytophagous bats (de la Peña‐Cuéllar, Stoner, Avila‐Cabadilla, Martínez‐Ramos, & Estrada, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those reported by Flynn et al., (2009), who found in a global meta‐analysis that the FD of nectarivorous birds may be retained in human‐dominated landscapes because of potential surplus flower availability in those environments. Also, the prevalence of some functional groups of fruit‐eating bats in deforested landscapes has been explained as the result of high dispersal capability and an ability to exploit the food supply provided by fruit trees, such as Ficus spp., in urban contexts (Farneda et al., 2015; Gonçalves et al., 2017; Jara‐Servín, Saldaña‐Vázquez, & Schondube, 2016; Klingbeil & Willig, 2009). For instance, deforestation may generate a variety of patches with different successional stages, which might increase fruit availability for several functional groups of phytophagous bats (de la Peña‐Cuéllar, Stoner, Avila‐Cabadilla, Martínez‐Ramos, & Estrada, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Independent variables are centered and standardized and middle-sized omnivorous bats and hematophagous species, had the highest values for those traits but were almost exclusively recorded in the areas with a high proportion of forest cover. In addition to considering traits related to flying performance as the mechanisms responsible for bat success in transformed landscapes, other aspects associated with habitat specialization, foraging behavior, food acquisition, and nutrient intake might play a crucial role in their adaptive capability (Jara-Servín et al, 2016;Saldaña-Vázquez, Ruiz-Sanchez, Herrera-Alsina, & Schondube, 2015;Welch & Beaulieu, 2018).…”
Section: Functional Traits and The Scale Of Effectmentioning
confidence: 99%
“…The abundance of large bats in transformed ecosystems (e.g. urban areas) has been explained because of the availability of nutrients and by the abilities that larger bodies confer (Jara-Servín et al 2017): for example stronger bites (Freeman and Lemen 2010) allow access to more food items. In our study landscape, for instance, Cecropia angustifolia is abundant in crops and other transformed areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, energy density was calculated for all food plants. Approximate values were obtained from previously published studies [ 8 , 12 , 16 , 32 ], the Australian Food Composition Database [ 33 ], or the U.S. Department of Agriculture FoodData Central Database [ 34 ] for crude fat (CF; S2 Table ). For any plant species where approximate CF values could not be found, a proxy value of 2.4% DM was used based on recommendations by Dairy One for CF in miscellaneous forages ( S2 , S4 and S6 Tables).…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral studies of frugivorous bats provide evidence that these animals require a variety of food plants to meet their nutritional requirements, including fruit, nectar, pollen, leaves and petioles [ 8 , 9 , 11 – 18 ]. Nutritional studies of frugivorous bat species have primarily focused on macronutrient content [ 12 , 13 , 19 21 ] and only a handful of studies reported micronutrient content of food plants consumed by flying-foxes [ 8 , 14 – 16 ] and the short-nosed fruit bat ( Cynopterus sphinx ) [ 17 ], limiting our ability to accurately predict nutrient requirements. Nutrient analysis of native food plants would provide evidence for how flying-foxes met their nutritional requirements historically and how the introduction of alien food plants might impact the nutrition of insular flying-foxes.…”
Section: Introductionmentioning
confidence: 99%